Expression of the MYB transcription factor gene BplMYB46 affects abiotic stress tolerance and secondary cell wall deposition in Betula platyphylla. Issue 1 (1st August 2016) - Guo, Huiyan; Wang, Yucheng; Wang, Liuqiang; Hu, Ping; Wang, Yanmin; Jia, Yuanyuan; Zhang, Chunrui; Zhang, Yu; Zhang, Yiming; Wang, Chao; Yang, Chuanping
Summary: Plant MYB transcription factors control diverse biological processes, such as differentiation, development and abiotic stress responses. In this study, we characterized BplMYB46, an MYB gene from Betula platyphylla (birch) that is involved in both abiotic stress tolerance and secondary wall biosynthesis. BplMYB46 can act as a transcriptional activator in yeast and tobacco. We generated transgenic birch plants with overexpressing or silencing of BplMYB46 and subjected them to gain‐ or loss‐of‐function analysis. The results suggest that BplMYB46 improves salt and osmotic tolerance by affecting the expression of genes including SOD, POD and P5CS to increase both reactive oxygen species scavenging and proline levels. In addition, BplMYB46 appears to be involved in controlling stomatal aperture to reduce water loss. Overexpression of BplMYB46 increases lignin deposition, secondary cell wall thickness and the expression of genes in secondary cell wall formation. Further analysis indicated that BplMYB46 binds to MYBCORE and AC‐box motifs and may directly activate the expression of genes involved in abiotic stress responses and secondary cell wall biosynthesis whose promoters contain these motifs. The transgenic BplMYB46‐ overexpressing birch plants, which have improved salt and osmotic stress tolerance, higher lignin and cellulose content and lower hemicellulose content than the control, have potential applications in the forestry industry.